Kumbang Badak sebagai Inspirasi Penciptaan Lukisan - Ajizul Hunafah Umri; Muslim Muslim (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study uses the rhinoceros beetle as the main subject in creating realism painting art because of its unique shape and strong symbolism of courage and resilience. In addition to having aesthetic value, the rhinoceros beetle also plays an important role in the ecosystem as a decomposer of dead wood and contributes to maintaining environmental balance. On the other hand, the existence of the rhinoceros beetle has cultural value in Indonesian society, especially in myths and traditional symbols. This study uses a qualitative-descriptive approach, with the process of creating works involving visual studies and symbolic interpretations. A total of three paintings were created by highlighting the morphological details of the rhinoceros beetle realistically and inserting symbolic meanings in its visual composition. The results of the study indicate that the rhinoceros beetle can be a source of inspiration in fine art and function as an educational medium to increase public awareness of the importance of preserving local fauna, especially insect species that are often overlooked.